Bones to ashes [compact disc, unabridged] - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2007)
Under the microscope, the outer bone surface is a moonscape of craters...'Preliminary diagnosis?' 'Deformity of the bone. Maybe. Cortical destruction on a metacarpal. Maybe. Localised infection? Systemic disease process? Postmortem destruction, either purposeful or natural? A combination of the above? I don't have a diagnosis...' The skeleton is that of a young girl, no more than fourteen years old - and forensic anthropologist Dr Temperance Brennan is struggling to keep her emotions in check. Coroner Yves Bradette is being evasive, insisting the bones are ancient and of no interest. But it doesn't quite add up, and a frustrated Tempe is convinced that Bradette is hiding something...It's not Tempe's case; she's overwhelmed with more urgent work in the lab...But the nagging in her subconscious won't let up. A memory triggered, deep in her hindbrain - the disappearance of a childhood friend; no warning, no explanation...Working on instinct, Tempe takes matters into her own hands. But she couldn't have predicted where this case would lead, or the horrors it would eventually uncover...Can Tempe maintain a professional distance as the past catches up with her in this, her most deeply personal case yet?